Simple Cholecystectomy Is Adequate for Patients With T1b Gallbladder Adenocarcinoma < 1 cm in Diameter - Wang, Zhengshi; Li, Yao; Jiang, Wenli; Yan, Jie; Dai, Jiaqi; Jiao, Binghua; Yin, Zhiqiang; Zhang, Yun (Frontiers in Oncology, 2019)
Purpose: Consensus-based clinical guidelines recommend that simple cholecystectomy (SC) is adequate for T1a gallbladder adenocarcinoma (GBA), but extended cholecystectomy (EC), SC plus lymphatic dissection, should be considered for T1b and more advanced GBA. Whether lymphatic dissection is necessary for treatment of T1b GBA remains controversial. This study attempted to better define the current criteria for local treatment of T1b GBA by examining the relationship between lymph node (LN) metastasis and tumor size in such patients. Patients and methods: Clinical data from patients with T1b GBA receiving curative surgical treatment between 2004 and 2015 were collected from the Surveillance, Epidemiology, and End Results (SEER) database. Baseline characteristics for the entire cohort were described, and overall survival (OS) and cancer-specific survival (CSS) were analyzed with the Kaplan–Meier method. Results: In total, 277 patients were enrolled for further analysis; 127 underwent lymphadenectomy. Among them, 23 patients had tumors <1 cm in diameter, none of which had LN metastasis; 104 patients had tumors ≥1 cm, 15 of which had positive LNs. In the group with tumor size <1 cm, there was no significant survival difference between treatment with SC or EC (P=0.694). Clinical benefit was observed in T1b GBA patients with tumor size ≥1cm receiving EC versus those receiving SC (P=0.012). Conclusion: SC was adequate for treatment of T1b GBA < 1cm in diameter. This evidence may be included as part of current guidelines.